2016
DOI: 10.7150/jca.13548
|View full text |Cite
|
Sign up to set email alerts
|

The Traditional Chinese Medicine Baicalein Potently Inhibits Gastric Cancer Cells

Abstract: Baicalein, a traditional Chinese medicine, is a member of the flavone subclass of flavonoids. It has been reported to have anticancer activities in several human cancer cell lines in vitro. However, the therapeutic effects of baicalein on human gastric cancer and the mechanisms of action of baicalein have not been extensively studied. In the present study, we utilized a cell viability assay and an in vivo tumor growth assay to test the inhibitory effects of baicalein on gastric cancer. Analyses of the cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…Baicalein is one of major flavonoids found in Scutellaria baicalensis . Previous studies have indicated that baicalein inhibits cell growth and metastasis and increases the sensitization of chemotherapeutic drugs via various pathways . However, few studies have reported changes in miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein is one of major flavonoids found in Scutellaria baicalensis . Previous studies have indicated that baicalein inhibits cell growth and metastasis and increases the sensitization of chemotherapeutic drugs via various pathways . However, few studies have reported changes in miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that baicalein induced cell cycle arrest at the S phase of division and promoted apoptosis in SGC-7901 gastric cancer cell lines via downregulation and upregulation of Bcl-2 and Bax levels, respectively. An in vivo study also revealed that baicalein excellently inhibited tumor growth in subcutaneous xenograft models [42]. Baicalein treatment inhibited the migration and invasion of GC cells in Transwell and wound-healing assays.…”
Section: Baicalein and Gastric Cancermentioning
confidence: 99%
“…Baicalein has been shown to inhibit cell growth and induce apoptosis in many human cancer cells including melanoma cancer (Lee et al ., 2005; Kim et al ., 2012; Li et al ., 2013; Wang et al ., 2014; Liu-Smith and Meyskens, 2016; Mu et al ., 2016). Although it has also been reported that baicalein reduces prostate, lung, breast, and liver cancer as well as osteosarcoma cell metastasis in vitro and/or in vivo (Wang et al ., 2010; Chen et al ., 2013; Zhang et al ., 2013; Gong et al ., 2014; Guo et al ., 2015), to the best of our knowledge, no studies have investigated the antimetastatic effect of baicalein in melanoma cells.…”
Section: Introductionmentioning
confidence: 99%